(untitled) (Journal of Ideas in Health, 2023)
Background: Primary testicular lymphoma (PTL) is an uncommon and aggressive form of extra-nodal non-Hodgkin lymphoma (NHL), accounting for <5.0% of testicular malignancies and 1.0% to 2.0% of NHL cases with a median age at diagnosis of 66 to 68 years. PTL accounts for 1–9% of testicular malignancies and 1–2% of NHLs. There are a handful of described lymphomas in the literature affecting normally positioned testis of aged men, yet none were reported in a cryptorchid middle-aged man. PTL is an extremely aggressive malignancy with poor progression-free survival and overall survival. Case presentation: A 47-year-old man presented to the urology clinic complaining of multiple painless swellings in the neck and groins. He also complains of back pain, drenching night sweats, a swollen right lower limb, constipation, anorexia, weight loss, and occasional vomiting. The illness’s duration is 2 months. He had a right inguinal testis. Histology examination of the excised testis and lymph nodes revealed an advanced “diffuse large beta-cell lymphoma” in both. The patient was referred for oncology care. Conclusion: It is an extremely rare case of Diffuse Large B-Cell Lymphoma (DLBCL) in the undescended testis of a middle-aged man. To the best of our knowledge, this is the first published case of its kind about the tumor’s type, testis anomaly, and patient’s age.